Peningkatan pemahaman ibu hamil tentang ASI eksklusif di kelurahan Gedung Johor Medan - Surya Anita; Dewi Bancin; Friska Sitorus (INDRA: Jurnal Pengabdian kepada Masyarakat, 2021)
: Understanding of pregnant women abouexclusive breastfeeding as evidenced by Exclusive breastfeeding is breastfeeding from birth until the child is 6 months old. During this period children are not expected to get additional fluids, such as formula milk, lemon juice, tea water, honey, and plain water. In exclusive breastfeeding, children are also not given additional food such as bananas, biscuits, rice porridge, teams, and so on. Exclusive breastfeeding for up to 6 months can meet the needs of children, and requires additional food at the age of over 6 months (Maryunani, 2012). The role of midwives in promoting exclusive breastfeeding can be started from the time the mother is pregnant. When pregnant women check their pregnancies, pregnant women will get information about the benefits of breastfeeding and how to successfully breastfeed when their babies are born (Atik, 2016). This activity was carried out in juni 2021, the Covid-19 pandemic then the participant who follows there were 20 mother pregnant and this activity went smoothly.